Double tree structure in a conducting body - Kobayashi, H.; Maeno, T.; Lorente, S.; Bejan, A. (International journal of heat and mass transfer, 2014)
In this paper we consider the fundamental problem of how to design the spacing between two plane and parallel tree structures buried in and transferring heat to a conducting medium. The Y and T tree-shaped structures are configured as two palms facing each other. The search for the optimal spacing is pursued in solid domains with three sizes. First, we studied a cube where the tree palms structure grow to the second level bifurcation. Second and third, we considered a small cube and a large cube where the tree structure consists of just the first level bifurcation. The results show that the best spacing between palms is half of the side of the cube, in order to avoid the interference between the two tree and adiabatic boundaries of the cube in which the trees structures are embedded. The spacing is possible to optimize, without being affected by the shape of the structure, the bifurcation level of the structure and the size of cube. The decision of optimal spacing is not affected by changes in the volume fraction occupied by tree structure in the conducting body.